Feed cost optimization for fattening cattle in Guanacaste, Costa Rica. - Barboza Navarro, David (2022)
Bovine meat is an important source of animal protein in Costa Rican households whose production chain faces the challenge of efficiently using scarce resources through the continuous improvement of their production processes and, at the same time, offering the quality that the market demands, without hurting your profitability. The objective of this research is to establish a mathematical model that allows minimizing the cost of feeding for the fattening of cattle from a diet based on forages, by-products and other supplements, in a farm located in Cañas, Guanacaste, Costa Rica. The linear programming method was used subject to restrictions according to cost and availability of different foods in the area. This made it possible to obtain different combinations of food inputs at the minimum cost, which guarantee to reach the nutritional levels required to achieve the daily weight gain established as a goal. The results showed that, through the mathematical model, it is possible to calculate rations that guarantee the nutritional requirements necessary for different objectives of daily weight gain, with a financial impact on the cost structure, since the use of available food resources is optimized in the area, which present a changing dynamic in the short term due to seasonal and market issues. Therefore, this combination of ingredients in the bovine diet allows to reduce the cost of production per kilogram and the time of the productive cycles to reach the required weight of the animals to go on the market. Due to the importance of the cost of feeding in fattening cattle, the control of supplementation is essential, in terms of both quantity and quality of nutrition.